Christ With Me: Prayers and Meditations from the Anglo-Saxon Tradition - Thurston, Bonnie Bowman (Cistercian studies quarterly, 2009)
The article reviews the book "Christ With Me: Prayers and Meditations From the Anglo-Saxon Tradition," edited and translated by Benedicta Ward.